Design of IoT-Based Digital Medical Record Devices in Medically Underserved Areas - Wirayudha, Ikhwan Adhi; Taqwa, Ing Ahmad; Handayani, Ade Silvia (Jurnal Teknologi Informasi dan Pendidikan, 2024)
Technological advancements have significantly impacted daily life, particularly in healthcare, where health monitoring devices play a crucial role. This device employs the MLX90614 sensor for measuring body temperature, an EKG sensor for heart rate monitoring, and the MAX30102 sensor for measuring blood oxygen levels. Data generated by these sensors are displayed on an LCD screen and managed using the Arduino Mega 2560 microcontroller. Test results show an impressive accuracy rate of 94.17%, indicating precise outcomes with relatively low error rates for each sensor: 1.05% for heart rate measurement, 2.0% for Spo2 errors with the MAX30102 sensor, and 2.78% for temperature errors with the MLX90614 sensor. With its enhanced capability for real-time and efficient health monitoring, this device has the potential to serve as a practical solution for routine health monitoring, offering significant benefits for maintaining overall health.